1989
DOI: 10.1037/0003-066x.44.10.1298
|View full text |Cite
|
Sign up to set email alerts
|

Rural America: Unique opportunities for health care delivery and health services research.

Abstract: A general deterioration is occurring in the quality of life of rural Americans, and it is affecting the quality of health and mental health service delivery. About 24% of the U.S. population lives in nonmetropolitan areas where the citizens are older, less well educated, have lower incomes, and are more homogeneous in terms of race and ethnicity. Medicare and private insurance discriminate against rural services in their reimbursement policies, and there is a shortage of health personnel in rural areas. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…A number of studies, however, demonstrate that problems in personal adjustment, psychological distress, alcoholism, illicit drug use and suicide are not appreciably less in rural areas (Coward et al, 1983;DeLeon et al, 1989;Furman & Selbyg, 1982;Wagenfeld, 1990). In a study on stress levels in a rural community, high levels of overall stress were found for both women and men.…”
Section: Rural Communities As Havens From Stressmentioning
confidence: 92%
See 1 more Smart Citation
“…A number of studies, however, demonstrate that problems in personal adjustment, psychological distress, alcoholism, illicit drug use and suicide are not appreciably less in rural areas (Coward et al, 1983;DeLeon et al, 1989;Furman & Selbyg, 1982;Wagenfeld, 1990). In a study on stress levels in a rural community, high levels of overall stress were found for both women and men.…”
Section: Rural Communities As Havens From Stressmentioning
confidence: 92%
“…But fewer physicians are available in rural communities (DeLeon et al, 1989), and because physicians in rural communities encounter women with HIV/AIDS less frequently (Lewis et al, 1987), they may be less familiar with risk assessment or treatment of HIV/AIDS in women. In fact, one study that compared AIDS in women in urban and rural Georgia found that the survival time for women in the urban area was signi cantly greater than that of women from areas outside Atlanta (Whyte & Carr, 1992).…”
Section: Issues In Service Deliverymentioning
confidence: 99%
“…At the time, prevailing concerns were the dearth of doctoral-level psychologists available at community mental health centers in rural areas, the lack of training of mental health professionals in the particular needs of rural residents, and the high rate of turnover in rural mental health positions (Hollingsworth & Hendrix, 1977). The federal government later recognized the health needs of rural Americans in 1987 when the Office of Rural Health Policy and the National Rural Health Advisory Committee were formed within the Health Resources and Services Administration (HRSA; DeLeon, Wakefield, Schultz, Williams, & VandenBos, 1989) with the mission of promoting both the physical and mental health of rural Americans. However, despite more than 30 years of focus on rural mental health, rural populations continue to face challenges in the receipt of psychological services.…”
mentioning
confidence: 99%
“…Most (73%) mental health resource shortages occur in rural areas (DeLeon, Wakefield, Schultz, Williams, & VandenBos, 1989). For example, although 10% of rural residents need psychiatric care, only 2-5% are actually treated (Flax, Ivens, Wagenfeld, & Weiss, 1978).…”
Section: Introductionmentioning
confidence: 99%